2017
DOI: 10.2147/ibpc.s128914
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence and its associated factors among hypertensive patients attending the Debre Tabor General Hospital, northwest Ethiopia

Abstract: BackgroundMedication adherence is an important predictor of optimal blood pressure control; hence, it significantly reduces the risk of cardiovascular disease (CVD) and associated deaths. However, studies on medication adherence and its associated factors are scarce. Thus, this study aimed to assess adherence to antihypertensive medications and identify associated factors at Debre Tabor General Hospital, northwest Ethiopia.MethodsA hospital-based cross-sectional study was conducted. Simple random sampling tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
91
6
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(113 citation statements)
references
References 20 publications
(24 reference statements)
12
91
6
4
Order By: Relevance
“…[23][24][25][26] In this study, patients with age <44 years old were three times more likely adherent than elderly patients. According to some reports in line with this study, younger patients showed better adherence to pharmacological treatment, 27 while others stated that young age is a determinant of poorer adherence to hypertensive medication. 12,25,26 Non-adherence in younger patients might be due to the lack of symptoms at early stages of the illness or more concerns about medication side effects.…”
Section: Discussionsupporting
confidence: 74%
“…[23][24][25][26] In this study, patients with age <44 years old were three times more likely adherent than elderly patients. According to some reports in line with this study, younger patients showed better adherence to pharmacological treatment, 27 while others stated that young age is a determinant of poorer adherence to hypertensive medication. 12,25,26 Non-adherence in younger patients might be due to the lack of symptoms at early stages of the illness or more concerns about medication side effects.…”
Section: Discussionsupporting
confidence: 74%
“…1,[5][6][7][8] It is one of the major, prevalent but modifiable risk factors, especially among patients with established cardiovascular disease (CVD) and cerebrovascular accidents. 2,9,10 As a result, HTN is the leading cause of morbidity and mortality among non-communicable diseases [11][12][13][14][15] and ranks third as a cause of disability-adjusted life-year causing about 7.1 million premature deaths each year. 11 Additionally, the complications of HTN account for 9.4 million deaths worldwide every year.…”
Section: Introductionmentioning
confidence: 99%
“…6,21 Even the prevalence of HTN has been increasing at an alarming rate among developing nations, especially in the African region. 15,22 The prevalence of HTN in Sub-Saharan Africa (SSA) has attained epidemic proportions likely due to the epidemiological transition and lifestyle modification with the adoption of western lifestyles. 23,24 In SSA, an estimated 74.7 million individuals are hypertensive and by the year 2025, the number of hypertensive individuals is projected to increase by 68% to 125.5 million individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, tough the study didn't focus on associated factors; it is most probable that education level of the study participants had a major influence of MMC as it was reported in study by Kripalani et al [6] and in the study which was conducted in Ethopia [13].…”
Section: Resultsmentioning
confidence: 99%